Semantic Interpretation of 3D Point Clouds of Historical Objects - Paul Cotofrei; Christophe Künzi; Kilian Stoffel (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2011)
This paper presents the main concepts of a project under development concerning the analysis process of a scene containing a large number of objects, represented as unstructured point clouds. To achieve what we called the ―optimal scene interpretation‖ ( the shortest scene description satisfying the MDL principle) we follow an approach for managing 3-D objects based on a semantic framework based on ontologies for adding and sharing conceptual knowledge about spatial objects.